Loss–Gain Framing Effects on Maize Farmers’ Contract Farming Decisions for Enhancing Farm Economic Sustainability - Rizky Yanuarti; Yuli Hariyati; Orawan Srisompun; Agus Supriono; Ebban Bagus Kuntadi; Ati Kusmiati; Titin Agustina; Suwali Suwali (Jurnal Agrinika: Jurnal Agroteknologi dan Agribisnis, 2026)
Maize is a strategic food commodity in Indonesia, yet smallholder farmers remain vulnerable to high price volatility and market uncertainty that threaten the economic sustainability of farm enterprises. Contract farming has been promoted as a mechanism to stabilize income and strengthen farmers’ market access, but participation remains uneven and may depend not only on structural factors but also on how contract benefits and risks are communicated. This study aims to examine how loss–gain framing affects maize farmers’ intentions to participate in contract farming and to identify the key determinants of actual participation. A quantitative survey was conducted with 120 maize farmers in Jelbuk Subdistrict, Jember Regency, East Java, selected through purposive sampling to represent both contract and independent farmers. Farmers evaluated contract messages framed as potential gains or potential losses using a five-point Likert scale, and differences in responses were assessed using paired non-parametric tests. Binary logistic regression was then applied to explain farmers’ contract participation decisions. The results show that gain-framed messages generated higher intention scores than loss-framed messages across both farmer groups, indicating that benefit-oriented communication is more persuasive. However, participation decisions were more closely associated with farm size, profitability, age, and education than with framing responses alone. These findings suggest that effective contract farming expansion requires both supportive economic conditions and communication strategies emphasizing tangible benefits to enhance farm economic sustainability.